Management in-class activities to enhance personal brand attributes of undergraduates - Paul, Anita * (Sunway College Kuala Lumpur, 2015)
The notion of personal branding, borrowed from a marketing concept, has intrigued many ever since Tom Peters coined the term in ‘the brand called you’(Peters,1997 as cited in Shepard 2005) . This led to the explosion of personal brand research by various enthusiasts. However, there exists limited academic literature on personal branding in the higher educational context but more references to personal development instead. This paper explores various researches on the concept of personal branding and explores its application in higher education the aims to enhance the awareness and development of personal branding attributes within the Management classroom.